A Systematic Review of the Effectiveness of Intergenerational Programs - Canedo-García, Alejandro; García-Sánchez, Jesús-Nicasio; Pacheco-Sanz, Deilis-Ivonne (Frontiers in Psychology, 2017)
Purpose of the study: The objective of the present review study is to identify the determinant elements of the effectiveness of empirically based interventions (EBI) in the field of intergenerational work, contrasting face-to-face and combined (face-to-face and virtual) intervention modalities against variables relating to this field according to EBI indicators. Design and Methods: An extensive literature search returned a total of 553 studies, of which just 50 met the inclusion criteria. Results: The descriptive and multivariate analysis conducted demonstrates that programs with a greater number of EBI controls have the greatest effectiveness, regardless of the intervention mode employed, and that this effectiveness is also modulated by other variables such as the participants' disabilities, their literacy level or membership to an organization. Conclusions: We examine the implications of these findings, noting the need to increase the number of virtual interventions that could improve the efficiency of the activities undertaken, while also ensuring that EBI indicators are fulfilled.